IMPLEMENTASI METODE MIND MAPPING DALAM MENINGKATKAN MINAT DAN PRESTASI BELAJAR SISWA TERHADAP MATA PELAJARAN BAHASA INDONESIA DI SMA NEGERI 1 KOTO GASIB - Sumirah Sumirah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
This study aims to determine the success of implementing the mind mapping method in increasing student interest and achievement in Indonesian subjects. The data collection technique of this research is observation, distributing questionnaires and daily tests. Observation data collection techniques using observation sheets about student learning interest and student completeness. The questionnaire distribution technique uses a questionnaire that will be filled in by students and the test technique uses a question sheet. The research method used is Classroom Action Research (PTK) with a research procedure of 2 cycles, each cycle for 3 meetings. The results of the study proved that students were very happy or enthusiastic about taking lessons using the mind mapping method. Students are also very active in following lessons. The teacher's appearance and the material presented are quite good, engaging and easy for students to accept. At the time of the test, all students seemed busy in doing the assignment and all students could complete the task well.